Mifepristone therapy in symptomatic leiomyomata using a variable dose pattern with a favourable outcome - Deepti Jain (Wolters Kluwer Medknow Publications, 2018)
Background: Leiomyomata causing symptoms have a deleterious effect on the health of women during reproductive age. Mifepristone, a progesterone antagonist was studied for reduction of symptoms in leiomyomata in perimenopausal women. Material and Methods: Mifepristone was adminstered to 7 women aged 47-50 years. Another 3 women less than 47 years were taken up for comparison of benefit of Mifepristone on leiomyomata related symptoms. Mifepristone was given in a stepwise declining dose for a period of 9 months to 1 year . The treatment was begun with 25 mg and the dose was reduced every 3 months. Every 3 months, the size of myomas, bleeding pattern, location of myomas, endometrial thickness, haemoglobin, and any side effects were all recorded. Results: There was considerable amelioration in the symptoms in both premenopausal as well as perimenopausal women, while mifepristone was continued. The reduction in myoma size was found to be statistically significant. After stoppage of drug in women aged 40-45 years, i.e. premenopausal group, the symptoms returned. However, in perimenopausal women, in 6 out of 7 women the symtoms abated completely and they had a smooth transition to menopause. Conclusion: Mifepristone is a very promising drug for conservative management of leiomyomata, especially in perimenopausal age (47years or more), where hysterectomy was averted in all 7 women.